Interaksi edukatif guru kunjung sebagai strategi alternatif meningkatkan motivasi belajar dalam pembelajaran masa pandemi COVID-19 - Meilisa Novariana (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2021)
The government policy through the Ministry of Education and Culture related to the pandemic period is the adjustment of learning during the Covid-19 Virus pandemic, where the learning process in schools that was initially carried out direct learning must be replaced with an online (online) and offline (offline) system. One of the things that must be in the mind of an educator in implementing this distance learning is to humanize the relationship. This best practice aims to describe the effectiveness of